Pengambilan Keputusan Pemberian Kredit Berdasarkan Karakteristik Nasabah dan Informasi Akutansi Pada PT. Bank Rakyat Indonesia (Persero) Cabang Rantauprapat - Syahrijal Hidayat (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Credit facilities provided by banks are the biggest assets for banks. Based on the author's observations at PT. Bank Rakyat Indonesia (Persero) Rantauprapat Branch at the time of pre-research it was known that the decline in credit realization was due to the low quality of accounting information held by customers. It can be seen that there are still many customers who do not have a good report on the company's health condition. So that in making the decision to grant credit at PT. Bank Rakyat Indonesia (Persero) Rantauprapat Branch is still based on trust and some use guarantees from large debtors or debtors who have been trusted by the bank. So that many prospective debtors based on the results of the assessment are not good, but because there is a guarantee from a third party, the credit application can still be realized. This results in a weak assessment of credit applications in looking at the characteristics and accounting information possessed by prospective debtors in making credit decisions, because some debtors do not need to go through credit analysis selection and financial statement assessment. Weak assessment causes weak credit decision making. Therefore we need a way of making decisions in granting credit. With the aim of making it easier for the bank to make credit decisions to colon customers. Based on the hypothesis testing is done by testing the partial significance test (t-test) and significant test. Simultaneously (f-test) where the calculation that the current ratio has a tcount value of 2.122 is greater than t-table 1.989 (tcount> ttable: 2.122>1.989) thus Ha is accepted while H0 is rejected. So it can be stated that the current ratio variable has a significant effect on = 0.05 on the decision to grant credit to the decision to grant credit. And the F value of 34,872, thus simultaneously the current ratio, return on equity, credit guarantee and debtor motivation variables have an Fcount of 34,872 which is greater than Ftable 2.483 (Fcount> Ftable: 35,383> 3,259). Thus, the effect of the independent variables (current ratio, return on equity, credit guarantees and debtor motivation) is simultaneously positive and significant on the dependent variable (credit granting decisions) at PT. Bank Rakyat Indonesia (Persero) Rantauprapat Branch.